EQUIVARIANT K-THEORY OF GRASSMANNIANS. (27th June 2017) - PECHENIK, OLIVER; YONG, ALEXANDER
Abstract : We address a unification of the Schubert calculus problems solved by Buch [A Littlewood–Richardson rule for the K -theory of Grassmannians, Acta Math .189 (2002), 37–78] and Knutson and Tao [Puzzles and (equivariant) cohomology of Grassmannians, Duke Math. J. 119 (2) (2003), 221–260]. That is, we prove a combinatorial rule for the structure coefficients in the torus-equivariant K -theory of Grassmannians with respect to the basis of Schubert structure sheaves. This rule is positive in the sense of Anderson et al. [Positivity and Kleiman transversality in equivariant K -theory of homogeneous spaces, J. Eur. Math. Soc. 13 (2011), 57–84] and in a stronger form. Our work is based on the combinatorics of genomic tableaux and a generalization of Schützenberger's [Combinatoire et représentation du groupe symétrique, in Actes Table Ronde CNRS, Univ. Louis-Pasteur Strasbourg, Strasbourg, 1976, Lecture Notes in Mathematics, 579 (Springer, Berlin, 1977), 59–113] jeu de taquin . Using our rule, we deduce the two other combinatorial rules for these coefficients. The first is a conjecture of Thomas and Yong [Equivariant Schubert calculus and jeu de taquin, Ann. Inst. Fourier (Grenoble) (2013), to appear]. The second (found in a sequel to this paper) is a puzzle rule, resolving a conjecture of Knutson and Vakil from 2005.